Monocytes of patients with amyotrophic lateral sclerosis linked to gene mutations display altered TDP‐43 subcellular distribution. (28th June 2016) - De Marco, G.; Lomartire, A.; Calvo, A.; Risso, A.; De Luca, E.; Mostert, M.; Mandrioli, J.; Caponnetto, C.; Borghero, G.; Manera, U.; Canosa, A.; Moglia, C.; et al.
Abstract : Aims: Cytoplasmic accumulation of the nuclear protein transactive response DNA‐binding protein 43 (TDP‐43) is an early determinant of motor neuron degeneration in most amyotrophic lateral sclerosis (ALS) cases. We previously disclosed this accumulation in circulating lymphomonocytes (CLM) of ALS patients with mutant TARDBP, the TDP‐43‐coding gene, as well as of a healthy individual carrying the parental TARDBP mutation. Here, we investigate TDP‐43 subcellular localization in CLM and in the constituent cells, lymphocytes and monocytes, of patients with various ALS‐linked mutant genes. Methods: TDP‐43 subcellular localization was analysed with western immunoblotting and immunocytofluorescence in CLM of healthy controls ( n = 10), patients with mutant TARDBP ( n = 4, 1 homozygous), valosin‐containing protein ( VCP ; n = 2), fused in sarcoma/translocated in liposarcoma ( FUS ; n = 2), Cu/Zn superoxide dismutase 1 ( SOD1 ; n = 6), chromosome 9 open reading frame 72 ( C9ORF72 ; n = 4), without mutations ( n = 5) and neurologically unaffected subjects with mutant TARDBP ( n = 2). Results: TDP‐43 cytoplasmic accumulation was found ( P < 0.05 vs . controls) in CLM of patients with mutant TARDBP or VCP, but not FUS, in line with TDP‐43 subcellular localization described for motor neurons of corresponding groups. Accumulation also characterized CLM of the healthy individuals with mutant TARDBP and of some patients with mutant SOD1 or C9ORF72 . In 5 patients, belonging to categories described to carry TDP‐43 mislocalization in motor neurons (3 C9ORF72, 1 TARDBP and 1 without mutations), TDP‐43 cytoplasmic accumulation was not detected in CLM or in lymphocytes but was in monocytes. Conclusions: In ALS forms characterized by TDP‐43 mislocalization in motor neurons, monocytes display this alteration, even when not manifest in CLM. Monocytes may be used to support diagnosis, as well as to identify subjects at risk, of ALS and to develop/monitor targeted treatments.